Pradigma Ilmu dalam Islam: Kritik terhadap Dualisme Ilmu Barat dan Islam - Aswatun Khasanah (Al-Widad, 2024)
This study aims to examine the paradigm of knowledge in Islam and analyze the criticism of the dualism of knowledge that has developed between Western and Islamic intellectual traditions. The research employs a library research method with a descriptive qualitative approach through the analysis of various works related to Islamic epistemology, philosophy of science, and the thoughts of contemporary Muslim scholars. The findings reveal that the dualism of knowledge emerged from the separation between religious sciences and secular sciences, influenced by the paradigm of Western secularism. From an Islamic perspective, knowledge is viewed as a unified entity originating from Allah SWT and developed through the integration of revelation and reason. The criticism of knowledge dualism is directed toward the tendency of modern science to neglect spiritual, ethical, and moral dimensions in the development of knowledge. As an alternative, Islam offers a tawhid-based paradigm of knowledge that harmoniously integrates rational, empirical, and spiritual aspects. This paradigm aims not only to achieve intellectual progress but also to promote human well-being and balance in life. Therefore, reconstructing the Islamic paradigm of knowledge is essential for developing a holistic, ethical, and relevant system of knowledge capable of addressing contemporary challenges.